Corporate governance, ownership structure and agency costs: evidence from Sri Lanka - Pratheepkanth Puwanenthiren; Balaputhiran Sathasivam; Velnampy Thirunavukarasu (Indonesian Management and Accounting Research, 2020)
The purpose of this paper is to examine the link between corporate governance, ownership structure and agency cost in Sri Lanka. The present study uses the regression model to analyse data for a sample of 150 firms listed in the Colombo Stock Exchange (CSE) for the financial years 2014 to 2018.  The empirical results show statistically significant and positive associations between board size, CEO duality, managerial ownership and agency cost proxies (i.e., asset turnover and expense ratio). The results also show a positive and significant relationship between the independent directors and asset turnover (though statistically insignificant with expense ratio), suggesting that, entrenched independent directors employ lower conflict of interest  in order to reduce the agency cost. Nonetheless, ownership concentration, was statistically insignificantly associated with agency costs, this paper provides support for such a view in Sri Lankan context. This study contributes to the literature on the on the association between corporate governance, ownership structure and agency costs. The findings may be useful for financial managers, investors, financial management consultants, and other stakeholders.